KURIKULUM CINTA DALAM PERSPEKTIF PENDIDIKAN KHOLISTIK: ANTARA MORAL, EMOSI, DAN RELASI SOSIAL PESERTA DIDIK - Nesa Apriyanti (Jurnal Komunikasi, 2026)
This study discusses the concept of the love curriculum in the perspective of holistic education within the development of Islamic Religious Education (PAI) curriculum. The focus of this study is on the integration of moral, emotional, and social dimensions in shaping students’ character comprehensively. The research uses a library research method by analyzing relevant books related to Islamic education, curriculum development, and educational psychology. The findings show that moral integration builds ethical awareness and noble character, emotional integration develops self-awareness and emotional regulation, while social integration strengthens students’ ability to build harmonious relationships. The love curriculum emphasizes a humanistic approach that places compassion as the core of the learning process. It aims to create a balanced educational process that does not only focus on cognitive achievement but also on affective and social development. Thus, the implementation of the love curriculum contributes to forming students who are intellectually, emotionally, and socially mature.